Corporate resource allocation : - Tomkins, Cyril (B. Blackwell, 1991)
Most books on allocating major corporate resources are written from just one viewpoint whether it be finance, strategy or behavioral science. Professor Tomkins argues that these important decisions obviously have multi-functional facets and implications. In this book he presents an integrated approach.